1995
DOI: 10.1159/000227467
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Cardioprotection with Cardioxane (ICRF-187) in Patients with Advanced Breast Cancer Receiving 5-Fluorouracil, Doxorubicin and Cyclophosphamide

Abstract: From January 1991 to August 1993,237 women with metastatic breast cancer were recruited into a multicentric phase II clinical trial designed to assess the cardioprotective activity of Cardioxane (ICRF-187). All patients were treated with 5-fluorouracil 500 mg/m2, doxorubicin 50 mg/m2, cyclophosphamide 500 mg/m2 (FDC) and Cardioxane 1000 mg/m2, in cycles repeated every 3–4 weeks. Cardiac functions were assessed at baseline by physical examination, ECG, and resting ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Dexrazoxane thus appears to protect against doxorubicin-induced cardiotoxicity without compromising treatment efficacy or patient health. Similar results have also been reported in patients with MBC at increased risk of cardiac events [65], and in patients receiving standard epirubicin therapy [66] or aggressive anthracycline-and taxane-containing chemotherapy [67]. The benefits of dexrazoxane have since been confirmed in two randomized, placebo-controlled, phase III studies in women with MBC being treated with FAC.…”
Section: Cardioprotective Agents To Prevent Anthracycline-induced Carsupporting
confidence: 68%
“…Dexrazoxane thus appears to protect against doxorubicin-induced cardiotoxicity without compromising treatment efficacy or patient health. Similar results have also been reported in patients with MBC at increased risk of cardiac events [65], and in patients receiving standard epirubicin therapy [66] or aggressive anthracycline-and taxane-containing chemotherapy [67]. The benefits of dexrazoxane have since been confirmed in two randomized, placebo-controlled, phase III studies in women with MBC being treated with FAC.…”
Section: Cardioprotective Agents To Prevent Anthracycline-induced Carsupporting
confidence: 68%
“…Generation of hydroxyl radicals by anthracyclines in the heart muscle may cause the cardiac toxicity. The cardioprotective effects of dexrazoxane have been demonstrated in patients in several studies (2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…There was no significant difference in time to progression and overall survival (OS) between the arms in both trials. Other randomized trials did not find a difference in RR [17,[21][22][23][24].…”
Section: American Journal Of Hematologymentioning
confidence: 97%
“…Multiple other randomized trials and a pooled analysis have not confirmed these findings [7,12,17,[21][22][23][24]26]. However, these studies enrolled mainly patients with solid tumors; the majority of them are adults with advanced breast cancer.…”
mentioning
confidence: 96%
See 1 more Smart Citation